KEWENANGAN OTORITAS JASA KEUANGAN UNTUK MENGATUR DAN MENGAWASI LEMBAGA PERKREDITAN DESA DI BALI - Yoga Bharata, Gde Putu Oka; Putra Astiti, Tjok Istri; Dewi Kasih, Desak Putu (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 2 No 2 (2017)DO - 10.24843/AC.2017.v02.i02.p15, 2017)
In general, financial institutions in Indonesia can be classified into the banking financial institutions and the non-bank financial institutions. One of the local financial institutions which currently growing rapidly in Bali are the Village Credit Institutions (LPD). In Article 1 point 11 of the Local Regulations Number 4 of 2012 on the LPD, LPD is clearly mentioned as financial institutions. The mention of LPD as financial institutions eventually led to uncertainty in the position of LPD to conduct the loan businesses. The business activities of LPD do have the similarities to those of the banking financial institutions, but on the other hand, if it is examined thoroughly, that there are fundamental differences that distinguish LPD with other financial institutions. The uncertain position of the LPD eventually causes problems with regard to the authority of the Financial Services Authority (OJK) in supervising the financial institutions. The type of the study is a normative legal research that explains the presence of uncertainty of the norm of the position of the LPD. The uncertainty of the position of the LPD, ultimately causing uncertainty about the authority of the OJK in overseeing the financial institutions. This study used primary, secondary, and tertiary legal materials. The results showed that the OJK does not have the authority to supervise the LPD, as they differ from other types of financial institutions. LPD is a cultural institutions with the nuance of Desa Pakraman community-owned economy. From the analysis conducted, it is more suitable for LPD to be classified as the village-owned enterprises. Therefore, although LPD is mentioned in the Local Regulation as a financial institution, it must be construed as the institutions that perform the financial function of the village, not as a financial institution of the certain individual or group of people ownerships, neither a commercial organization that is entirely profit oriented.